Identifikasi Cendawan Penyebab Penyakit Pascapanen pada Beberapa Buah di Yogyakarta - Ani Widiastuti; Ovianne Hapsari Ningtyas; Achmadi Priyatmojo (Jurnal Fitopatologi Indonesia, 2015)
In Indonesia, high yield losses due to post-harvest diseases are often difficult to measure because research focusing on such matter are still limited. This study aimed to determine the genera of fungi that cause rot on postharvest fruit, which can be used as a basis to determine the important pathogens in the current post-harvest commodities and for further disease management. The method used is sample collection, single spore isolation, microscopic observation and identification of fungal genera. Colletotrichum sp. was sucessfuly isolated from antrachnose of papaya. Pestalotia sp. was found in the fruit rot of avocado and star fruit. Lasiodiplodia sp. was found in mango, while Pestalotia sp. and Lasiodiplodia sp. was found in both sapodilla and banana. Alternaria sp. was found in the fruit rot of pears and apples. Aspergillus sp. was found in grapes, and Fusarium sp. was isolated from pineapple fruit rot.